Leading in tough times overcome even the greatest challenges with courage and confidence - Maxwell, John C. (New York Center Street, 2021)
Great leaders will face challenges. Markets will collapse; pandemics will come; people will always provide new and interesting ways to makes things difficult. But leaders must achieve results and build a team that produces, even when you are faced with difficult circumstances. This all-new book from John Maxwell, created using content from several of his previous bestselling titles, is the ultimate guide to helping your team survive and even thrive when the unexpected happens. Maxwell helps leaders identify their team's main challenges, take stock of their liabilities, understand what they can control, and use challenges as opportunities to rethink the way they do things. He ultimately gives leaders the tools to grow their teams in the midst of difficult times. Using humor, in-depth insight, and examples, internationally recognized leadership expert John C. Maxwell reassures leaders that they can still lead well and help people develop the skills they need to become great leaders, even when times are tough
Includes bibliographical references.
Keywords: Executive ability